Uwagi na temat astronomicznej interpretacji układu kręgów kamiennych z okresu rzymskiego w Odrach - Borczyk, Wojciech (Acta Universitatis Lodziensis. Folia Archaeologica, 1996)
Results of astronomical and geodetical measurements made in the „Stone Circles” reserve at Odry are presented. The aim of the measurements was to test the hypothesis about the astronomical significance of the circles. Preliminary results seem to suggest that there was no close correspondence between the orientation of the circles and the points of sunrises and sunsets during the summer and winter solstices over the past 4000 years.